Prevalence of Autism Spectrum Disorder and Co-morbidities in Children and Adolescents: A Systematic Literature Review - Bougeard, Clémence; Picarel-Blanchot, Françoise; Schmid, Ramona; Campbell, Rosanne; Buitelaar, Jan (Frontiers in Psychiatry, 2021)
Objective: Individuals with autism spectrum disorder (ASD) often present somatic and/or psychiatric co-morbid disorders. The DSM-5 allows for consideration of additional diagnoses besides ASD and may have impacted the prevalence of co-morbidities as well as being limited in capturing the true differences in prevalence observed between males and females. We describe the prevalence of ASD and frequently observed co-morbidities in children and adolescents (< 18 years) in the United States and five European countries. Methods: Two systematic literature reviews were conducted in PubMed and Embase for the period 2014-2019 and focusing on the prevalence of ASD and nine co-morbidities of interest based on their frequency and/or severity: Attention Deficit Hyperactivity Disorder (ADHD), anxiety, depressive disorders, epilepsy, intellectual disability (ID), sleep disorders, sight/hearing impairment/loss and gastro-intestinal syndromes (GI). Results: Thirteen studies on prevalence of ASD and 33 on prevalence of co-morbidities were included. Prevalence of ASD was 1.70% and 1.85% in US children aged 4 and 8 years respectively, while prevalence in Europe ranged between 0.38% and 1.55%. Additionally, current evidence is supportive of a global increase in ASD prevalence over the past years. Substantial heterogeneity in prevalence of co-morbidities was observed: ADHD (0.00% - 86.00%), anxiety (0.00% - 82.20%), depressive disorders (0.00% - 74.80%), epilepsy (2.80% - 77.50%), ID (0.00% - 91.70%), sleep disorders (2.08% - 72.50%), sight/hearing impairment/loss (0.00% - 14.90% / 0.00% - 4.90%) and GI syndromes (0.00% - 67.80%). Studies were heterogeneous in terms of design and method to estimate prevalence. Gender appears to represent a risk factor for co-morbid ADHD (higher in males) and epilepsy/seizure (higher in females) while age is also associated with ADHD and anxiety (increasing until adolescence). Conclusion: Our results provide a descriptive review of the prevalence of ASD and its co-morbidities in children and adolescents. These insights can be valuable for clinicians and parents/guardians of autistic children. Prevalence of ASD has increased over time while co-morbidities bring additional heterogeneity to the clinical presentation, which further advocates for personalized approaches to treatment and support. Having a clear understanding of the prevalence of ASD and its co-morbidities is important to raise awareness among stakeholders.